2014
DOI: 10.1142/s0217732314501296
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic effects on the inhomogeneity of planar symmetry

Abstract: In this work, we aim to identify the effects of electromagnetic field on the energy density inhomogeneity in self-gravitating plane symmetric spacetime filled with imperfect matter in terms of dissipation and anisotropic pressure. We formulate the Einstein–Maxwell field equation, conservation laws, evolution equations for the Weyl tensor and the transport equation for diffusion approximation. Inhomogeneity factors are identified for some particular cases of non-dissipative and dissipative fluids. For non-dissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…Di Prisco et al [7] investigated the dynamical properties of an a e-mail: msharif.math@pu.edu.pk b e-mail: zeeshan.math@pu.edu.pk anisotropic spherical matter distribution and found that small fluctuations of the pressure anisotropy lead to system cracking. Sharif et al [8][9][10][11][12][13][14][15] analyzed the effects of anisotropy on the dynamical properties of spherical as well as non-spherical dense relativistic distributions and found very complicated system phases due to the presence of anisotropy. Sunzu et al…”
Section: Introductionmentioning
confidence: 99%
“…Di Prisco et al [7] investigated the dynamical properties of an a e-mail: msharif.math@pu.edu.pk b e-mail: zeeshan.math@pu.edu.pk anisotropic spherical matter distribution and found that small fluctuations of the pressure anisotropy lead to system cracking. Sharif et al [8][9][10][11][12][13][14][15] analyzed the effects of anisotropy on the dynamical properties of spherical as well as non-spherical dense relativistic distributions and found very complicated system phases due to the presence of anisotropy. Sunzu et al…”
Section: Introductionmentioning
confidence: 99%
“…We investigated the role of isotropic as well as anisotropic pressure in cylindrical and planar collapsing geometries coupled with non-adiabatic fluid models [12,13]. Sharif and Bhatti studied effects of physical variables known as inhomogeneity factors in the radiating and non-radiating planar [14][15][16][17][18], cylindrical [19][20][21], spherical [22,23] and axial [24,25] collapse. Arbuzova et al [26] obtained collapsing spherical models and concluded that dark sources due to modified gravity cause repulsion among massive bodies which lead to the formation of relatively thin shells.…”
Section: Introductionmentioning
confidence: 99%
“…We choose a non-static planar geometry for the construction of our systematic analysis as [38][39][40][41] …”
Section: F (R) Gravity Coupled To Matter Sourcementioning
confidence: 99%